An efficient ALOHA based collision resolution algorithm for RFID - S. K. Wijayasekara (2020)
© 2020 IEEE. This paper describes a frame-based anti-collision algorithm which is compatible with the current RFID standard of EPCglobal Gen-2 that employs a frame slotted ALOHA approach to detect the tags. The proposed algorithm is derived from the existing tree-based algorithm, called Bayesian Estimation based Modified Dynamic Tree (BE-MDT) [1]. We also derived a mathematical model for our proposed algorithm. The outcomes from the given numerical model and simulation verify that the proposed method accomplishes a higher system efficiency and time system efficiency in tag identification and outperforming the currently employed conventional frame-based collision resolution algorithm in EPCglobal Gen-2 standard.